Exposure of Muscle Tissue to the field from a Dipole Array Antenna - R.Swaminathan, Reji, P.Muthukannan (International Journal of Advanced Science and Technology, 2020)
Various bands of Electromagnetic radiations cause severe health effects to people. Number of devices emits radiation in all segments of the society.In this paper the exposure of a muscle tissue to the fields from a Half wave dipole antenna is studied. A Dielectric named Muscle parallel fiber ovine is created in the software and an array antenna with three elements is placed at certain distance to analyze its field effects on the Muscle Tissue. Parameters like SAR, Electric field will be plotted and also antenna parameters like VSWR, Reflection coefficient will be calculated. Antenna resonates at a frequency of 900MHz.The calculation of Electric field, SAR and the plot of far field demonstrates the exposure of the muscle tissue to field from antenna.Keywords: Antenna, Muscle Tissue, Radiation, SAR, VSWR.